The underwater planet (Spacemice, 6,, 2016)
Geronimo Stiltonix and the spacemice follow a treasure map to the planet Aquarix, unlock a treasure chest of rare material that powers an entire underwater civilization, and prevent pirate spacecats from stealing the chest for themselves.